11 Jul
11 Jul
11 Jul
Factorize
following polynomials
K x2 + 2x + 1 = (x + 1)2
A b C
M
it 2x
↑
check b2 X
X 2
+
4a : 0
,
-
S
-
4 -
421)(2) : 4
- . X +
2x + 3 : check 4-4(1) (12) : 8 X
* x2x + 1 = (x -
1)2
x 2x check
X 2 4-4(1) 2-2)
- -
S
: 1320
"
P x 2x -
3 =
(x -
3)(x +
1)
X
.
x2 2x =
x(X -
2)
S 12 + 9x + 12
S
.
x+ 4 .
5x + 2
x-(x + 1
⑯ - 2 + 14x + 7 = -
x(x -
2x -
1)
M x8 256 for
degree
-
.
enou 2
.
1 62 b2-4ac ? O
542
⑪ -
+ 154 + 6
2
.
3
.
Es so
esogg
sas
3 . I .
28 2
58uim
⑬x2 + x + 5 \a cab + bi
+
a2 -zab + b2
3 . 2 wooing no .
2
14 4x2 y =
256
+
32y
-
x2 4y2
⑮ - -
4x +
4y + 3
⑪ (2x2 23 -
+ 8
14472a 3)2
·
%
16a -
-
(
Solve these equations!
19
. (3x-11)(X -2) + 137 =
10(2x -
19 -
(2x -
3)(x + 4)
·
20 (7X -
522 =
(5x -
7) (10x + 9) -
33x + 37
21 . 1694 -
1824 + 38 =
6479 + 146x + 110
29 1 I 1 I
.
+ =
+
1 +
1 6 + 1 C + 1 3 + 1
23 ↓ T I
.
I 1 +
t
2 + E 5 + E 3 + 4 + E
24 X + 2 +
1 :
0
.
25 .
(x -
5)" -
(E + 5) :
0
-
-
(4a
-
5b)(3a + 2b)
-
Iza"-cab-lob :
12(a-cab-l :
(2)(a) +
↳ a ↓ b
-
8 + 38 -
30 :
0
- ( 2 19)
- - -
2) -
30 ⑪
11
,
12
,
Es ,
15 16
,
110 115
,
130
, ,
100
2 2
2x + a) a)
g(x -
2x 1)h s(X 2
x
+ -
1)
5 .
-
2x -
= X* -
2x + 1 -
3
① a. 2
Serie
: (x-1)2 -5
1)/@
!
: (x-1-5)(x-1 +
woons
6 .
X -
2x -
3
:
(x2-2x + 1) -
4 =
0520in
2
: (x-12 - = 02
= (v -
1 -
2)(x -
1 + 2)
-
(x -
3)(X +
1)
(x - as = x2-2ax + a
x
c . + gx + 12
(x a) + = xi + 2ax
-
+ al
2ax =
9X
(g)2)
3
(x
a :
=
+
2x
+ -
(2) + 12
=
(x +
92 -
G +
·
(x
+ 9
(x (x
9 +
· + 9 +
losus 2
#
g .
x2 + 4 .
5x + 2
x + 4 5x
. + 2 =
0
Step 1 :
Socia 2x + 9x + 4 :
0
=
(2x + gx +
4) : x2 +
2x + 2
: (20 +
1((x + 4) =
x +
2)x (2) + -
( +
:
(x +
9) _
(x
2)(X
+
+
: -
+
(x
1)(x 4)
=
+ +
11 .
x8 -
256 (a) :
a
"
(a3)(a) : as
8
=
x - 162
:
(x4)2 -
163 x + ad
,
check 62-4ac
:
(x4 16)(x4 -
+ 16) o-
4(1)(a)
4) (( * )
"
(6% 49/0
-
-
*
· (8 4)(x2 + 4)(x
-
+ 16)
>
- ** A
(x- 2)2
* =
: x
<(a)(x) + 22
-(x -
10) 16)
e (y 16)(y (y
- - = -
: 4x2 -
(ya -
32y
+ 256)
4X" ( y 16)9
-
:
at b2 b)(a
(5x5 <y -16)d
(a + b)
-
-
=
-
= (2x -
(y 16))(2x -
+
(y -
16))
=
(2x y 16)(2x + 16)
y
+
-
-
x2 4y2 4x 3
15
4y
.
- - + +
:
(x ** ] -x +
1 by -
+
4y
+
3) -
:
(x -
2) +
( -
4y 4y 1) + -
= (x -
2) -
(4y2 4y +
1) Steps : 16-4(4)(1)20
(2y 1) 1)
~ Step 2 : Asoso 4(y -
y +
)
(2y
- -
((y (1) ( +
=
~
Steps : 4 <
(y)(2)
(x-2
+
(2g- 13.
-
-
: -
(x 4((y E)2 i 4) - -
+
2
2y 1)(x + 2 +
2y 1)
-
-
: -
-
=
(x
2y 1)(x +
3) 4(y
-
2)
zy
- -
-
10
. .. (x-2x -
1)
a zab + b = (a -
b)
-
-
c(x -
2(x)(x) + 1 -
2)
: - (x -
12 - E
:
-
c(x -
1 -
v)(x -
1 + m)
19 . - 542 + 154 + 6
:
-
5(x2 -
3x -
G
a -
2(a)(b) +
b2
5)(X 3)
-
: -
5/(X- -
-
:
5 (X-3-f)(X-
-
P
1. a - b3 = (a -
b) (a + ab b) +
a + b3 bi
=
ab
(a b) (a
+
.
2 =
+
1. . a zab + bi
+ =
(a + b)
2
. a-zab b + = La- by
3. a
:
-
b2 =
(a + b) (a - b)
16 . (2x2-2)3 + * 2
=
(2x2 -
2 + 2) ((0x222 - (2x 2)(2) + 4)
=
(2x =
+ x)(4x4 -
8x + 4 -
4x + 4 + 4)
(4x" 1242
*
: 2x -
+ 12)
: A
62 -
4ac = 9-12 ? 0
= 8x4X4 3x4 3) -
+
X
A2 -
31 +
3
A2 - B2 A = 494 B : 12 (2013)
, ,
14472a 3)2
%
17 .
16a -
-
=
(4a4 -
12 (2a? 3)) (4a4 + 12(2a 3)) -
=
(4a4 -
2492 +
36)(4a4 + 24a -
36)
g)
:
16 (at 3)2(a2 -
% ((a + ? )
18 .
(1) +
> a + b
,
a =
( ) ,
b =
-
+
(2)-
:
(E) -3 )
(x% (x
+
3x 3)
=
-
+
-
= (10x -
2) -
(36x + 60)3
= (100 -
2 -
36x -
60)(10x -
2 + 36x + 60)
= ( -
264 -
623(46x + 58)
=
4) -
13x -
31)(237 + 29)
O O
3
4) (in) - m()
41 (i -
[i]
x? a
: b
, y
4) a -
85ab +
44162
(a)
·
-
z(cal
(8b) +
185b) -
(b) +
4416
"